2021
DOI: 10.1002/anie.202103085
|View full text |Cite
|
Sign up to set email alerts
|

Late‐Stage Heteroarylation of Hetero(aryl)sulfonium Salts Activated by α‐Amino Alkyl Radicals

Abstract: We report a late-stage heteroarylation of aryl sulfonium salts through activation with a-amino alkyl radicals in a mechanistically distinct approach from previously reported halogen-atom transfer (XAT). The new mode of activation of aryl sulfonium salts proceeds in the absence of light and photoredox catalysts, engaging a wide range of hetarenes. Furthermore, we demonstrate the applicability of this methodology in synthetically useful cross-coupling transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(33 citation statements)
references
References 49 publications
1
31
0
1
Order By: Relevance
“…In 2020, Leonori and co-workers reported a new chemical strategy for carbon radical generation involving α-aminoalkyl radicals as halogen-extraction reagents. In addition, Ritter and co-workers recently reported that α-aminoalkyl radicals act as strong reductants to reducing TT-salts to aryl radicals.…”
mentioning
confidence: 85%
“…In 2020, Leonori and co-workers reported a new chemical strategy for carbon radical generation involving α-aminoalkyl radicals as halogen-extraction reagents. In addition, Ritter and co-workers recently reported that α-aminoalkyl radicals act as strong reductants to reducing TT-salts to aryl radicals.…”
mentioning
confidence: 85%
“…Over the past couple of years, our group has introduced a highly regioselective arene C–H functionalization to access aryl thianthrenium salts; the thianthrene substituent serves as a versatile linchpin for further manipulation, including C–F bond formation . The most practical reaction with promise for fluorine-18 translation was obtained when we switched from the thianthrene scaffold to the dibenzothiophene scaffold .…”
Section: Discussionmentioning
confidence: 99%
“…9f In 2021, the Ritter group developed a methodology for heteroarylation using aryl thianthrenium salts as radical precursors via a radical addition process (Scheme 14 ). 22 Here, the C–S bond is activated with α-aminoalkyl radicals. The reaction proceeds under simple and air-moisture tolerant conditions with Na 2 S 2 O 8 and a tertiary amine, no light or photoredox catalyst was required in this system.…”
Section: Thianthrenation-enabled Site-selective Functionalization Of ...mentioning
confidence: 99%